STRUCTURAL ANALYSIS AND DESIGN APPROACHES FOR A NON-CONTACT ROTATIONAL DRIVE ON GAS-LUBRICATED SUPPORTS AS A SINGLE AND ADJUSTABLE DYNAMIC SYSTEM - Breshev, Oleksii; Bashta, Oleksandr; Nosko, Pavlo; Kharchenko, Andrii; Herasymov, Volodymyr; Ladyk, Anton (Problems of Friction and Wear, 2024)
The paper presents a comparative analysis of the designs of non-contact rotational drives on gas-lubricated bearings used in machines and mechanisms for various purposes, such as microturbine generators, two-axis displacement tables, pneumatic spindles, and single-crystal cutting machines. The technical and technological advantages of non-contact direct rotational drives with gas-lubricated bearings are shown; the use of a non-contact drive with an aerostatic bearing in precision positioning mechanisms results in a uniform (smooth) movement with maximum positioning accuracy of the actuator. The approaches to designing the drive as a single and adjustable dynamic system, the characteristics of which are established and adjusted by changing the design, technological parameters, and adjusting the aerostatic supports, are considered. Based on the research, the directions of technical improvement of drives on gas-static supports which allow to maximize the existing advantages and features of gas-lubricated supports are outlined.